2018
DOI: 10.1021/acsami.8b01725
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Assembly of a Peptide Gelator and Silk Fibroin Afford an Injectable Hydrogel for Tissue Engineering

Abstract: Silk fibroin (SF) from Bombyx mori has received increasing interest in biomedical fields, because of its slow biodegradability, good biocompatibility, and low immunogenicity. Although SF-based hydrogels have been studied intensively as a potential matrix for tissue engineering, weak gelation performance and low mechanical strength are major limitations that hamper their widespread applicability. Therefore, searching for new strategies to improve the SF gelation property is highly desirable in tissue engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 59 publications
1
74
0
Order By: Relevance
“…The quick gelation process of SF‐RGD gel was triggered by the cooperative intermolecular interaction assembly of NapFFRGD gelator and SF molecules in water aided by hydrophobic and hydrogen bonding. These interactions can further induce the molecular conformational transformation of SF from random coils to the β‐sheet conformation, thus resulting in its rapid gelation . Rheological tests revealed that the obtained SF‐RGD gel exhibited typical viscoelastic behavior of hydrogels, as exemplified by the threefold higher storage moduli ( G ' = 6679 Pa) of SF‐RGD gel in relation to its loss moduli ( G ” = 1742 Pa) within the investigated oscillating frequency range from 0.1 to 100 Hz (Figure d).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The quick gelation process of SF‐RGD gel was triggered by the cooperative intermolecular interaction assembly of NapFFRGD gelator and SF molecules in water aided by hydrophobic and hydrogen bonding. These interactions can further induce the molecular conformational transformation of SF from random coils to the β‐sheet conformation, thus resulting in its rapid gelation . Rheological tests revealed that the obtained SF‐RGD gel exhibited typical viscoelastic behavior of hydrogels, as exemplified by the threefold higher storage moduli ( G ' = 6679 Pa) of SF‐RGD gel in relation to its loss moduli ( G ” = 1742 Pa) within the investigated oscillating frequency range from 0.1 to 100 Hz (Figure d).…”
Section: Resultsmentioning
confidence: 92%
“…However, its slow gelation rate and the shortage of biochemical cues to direct cell adhesion, proliferation, and differentiation significantly affects its application potentials in biomedical fields. Therefore, peptide gelators were incorporated into SF to significantly improve its gelation properties through cooperative molecular assembly in liquid phase . In order to generate a SF gel with a high gelation rate and improved biochemical cues, we synthesized NapFFRGD, a small peptide gelator, and introduced it to the SF solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] In early 1960, O. Wichterle et al reported the rst case of hydrophilic gels, 12 many studies have been focused on applications in wound healing via using hydrogels. [13][14][15][16][17][18] Increased evidence showed hydrogels can deliver cytokines and growth factors, 19 which is benecial for burn wound healing. Also, hydrogels are good stain removers, [20][21][22] and they are nonadherent and can engulf bacteria, which is benets to threedimensional (3D) network expansion upon exudate absorption.…”
Section: Introductionmentioning
confidence: 99%